Variation of the athletic performance in qualified wrestlers in Greco-Roman wrestling by their level of functional skills - Podlivaev, B. A.; Korzhenevsky A. N. (International Journal of Wrestling Science, 2013)
Competitive activity in Greco-Roman wrestling is very demanding with regard to anaerobic and aerobic performance in the area of zone glycolytic energy supply. Improving athletic performance is often associated with increasing the energy capacity of athletes (5, 6, 7). The physical state of the central nervous and neuromuscular systems of wrestlers also must meet high demands (8). Few studies have been conducted in which the changes in the CNS and the NMS of Greco-Roman wrestlers of differing qualifications identified the influence of competitive training (2). Studies relating to comprehensive research concerning energy adaptation and analyzing systems limited to non-specific training for qualified wrestlers depending on the level of athletic performance in important competitions so far have not been found.The purpose of the study. Identify the features of adaptation to the highly non-specific training of Greco-Roman wrestlers, characterized by different levels of athletic achievement.